Establishment of Reference Intervals for Thyroid-Associated Hormones Using refineR Algorithm in Chinese Population at High-Altitude Areas - Ma, Chaochao; Zhong, Jian; Zou, Yutong; Liu, Zhijuan; Li, Honglei; Pang, Jinrong; Liu, Xiaoxing; Zejipuchi,; Tian, Liping; Hou, Li’an; Wang, Danchen; Cheng, Xinqi; et al. (Frontiers in Endocrinology, 2022)
Objectives: Diagnosis of thyroid disease among individuals dwelling at high-altitude remains challenge. Reference intervals (RIs) for thyroid-associated hormones among Tibetan living at various high altitudes were established to improve diagnosis. Methods:1281 subjects were randomly recruited from Nyingchi, Shigatse/Lhasa and Ali of Tibet. Thyroid stimulating hormone (TSH), free triiodo-thyronine (FT3) and free thyroxine (FT4) were measured by Cobas e601 electrochemiluminescence analyzer. We used the multiple linear regression and variance component analysis to assess the effect of sex, age and altitude on hormones. RIs were established by RefineR algorithm and compared with those provided by manufacturer. Results: Serum TSH was significantly lower in male than in female, while FT3 and FT4 were higher in male. Both FT3 and FT4 decreased with increasing age. FT3 increased with altitude, while TSH and FT4 were less influenced by altitude. The RI for TSH was0.764-5.784μIU/mL, while for FT4 were12.36-19.38pmol/L in female and14.84-20.18pmol/L in male. RIs for FT3 at Nyingchi, Shigatse/Lhasa, Ali in female were4.09-4.98,4.31-5.45 and4.82-5.58pmol/L, while in male were4.82-5.41,4.88-5.95,5.26-6.06pmol/L, respectively. Obtained RIs for TSH and FT4 were generally higher while that for FT3 was narrower than RIs provided by Cobas. Conclusions: Specific RIs were established for thyroid-associated hormones among Tibetan, which were significantly different from those provided by manufacturer.